Multimodality Imaging in Transcatheter Mitral Interventions - Nikolou, Evgenia; Bilkhu, Rajdeep; Kafil, Tahir S.; Demetrescu, Camelia; Kotta, Prasanti Alekhya; Lucchese, Gianluca; Tzemos, Nikolaos; Grapsa, Julia (Frontiers in Cardiovascular Medicine, 2021)
Multimodality imaging is of imperative value for the planning and guidance of transcatheter mitral valve interventions. This review employs the value of different imaging modalities and future implications for clinical practice.